Silica-Xerogel Coated Cotton as Multifunctional Textile: Development and Characterization. Issue 1 (1st January 2023) - Assal, M.; El Wazna, M.; Oumghar, K.; El Bouchti, M.; El Bouari, A.; Cherkaoui, O.
Abstract: Silica xerogel has attracted increasingly more attention in the field of thermal insulation as its extraordinary properties such as thermal conductivity, fire resistance, hydrophobicity and low density. This work focuses on the development of new insulating material, based on the xerogel as charge for cotton fabric. The composite was developed using vacuum molding process. The microstructure has been determined in each materials using SEM observations, and have a good hydrophobicity which the contact angle is 125°. The results obtained from this study can be useful to develop new low cost, sustainable, light product, insulation and environmentally friendly materials.